9x+3=6x-5

Simple and best practice solution for 9x+3=6x-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9x+3=6x-5 equation:



9x+3=6x-5
We move all terms to the left:
9x+3-(6x-5)=0
We get rid of parentheses
9x-6x+5+3=0
We add all the numbers together, and all the variables
3x+8=0
We move all terms containing x to the left, all other terms to the right
3x=-8
x=-8/3
x=-2+2/3

See similar equations:

| 8+XxX=268 | | 3|4x-13=2 | | 0.2x+-9=0.8x+12,x | | 4x+6+3x-2x-5=6 | | 5/4t+6=-14 | | (7w-7)=(3w+7) | | C=10n+12 | | 5p+.25(p+16)=4+.75p | | .5p+.25(p+16)=4+.75p | | (e-14)/8=10 | | (a-4)/3=9 | | (d+14)/12=2 | | (d+8)/3=3 | | -8+12x=10x+10 | | 9(s-10)=99 | | 7(u-2)=70 | | 5(j+5)=65 | | (47-32)x5/9=°C | | 3(e+1)=15 | | 4/5x+13=9 | | 4x+4-x=-8 | | 7.5/x=3 | | 52=4/7x | | 5/4t+6=14 | | y-7-1=8 | | 2(x+4=38 | | -10r+4r+3r=8+4r | | −51=−3+8c−51=−3+8c | | −8=32−5q | | 5y+5+(2y+4)=11y-15 | | 12v-14+3v=1 | | s/6-12=-8 |

Equations solver categories